How Philosophy Lecturers Connect Ideas To Personal Development Through Lived Philosophical Practices - Ratna Roshida Ab Razak; Mohd Yusoff A. N; Muhammad Z.; Maslan A.; Mokhtar R.A.; Muhammad Hafeez Zakaria (Universiti Sains Malaysia, 2026)
Non-Indexed Publication